Kārikāvalī : Muktāvalīsahitā, sā ca Prabhā-Mañjūṣā-Dinakarī-Rāmarudrī-Gaṅgārāmīti vyākhyāpañcakasamanvitā - Viśvanātha Nyāyapañcānana Bhaṭṭācārya (Vrajajīvana prācya bhāratī granthamālā, 1988)
Verse treatise, with autocommentary and supercommentaries, on the basic concepts and epistemology of Nyāya and Vaiśeṣika schools in Indic philosophy.